Late Palaeozoic South American pectinids revised: biostratigraphical and palaeogeographical implications - Neves, Jacqueline P. (2014)
A revision of the late Palaeozoic South American pectinid Heteropecten multiscalptus (Thomas) and the establishment of Heteropecten paranaensis sp. nov. have important implications for the relationship between faunal realms within South America. Late Palaeozoic bivalve faunas occur in three distinct realms in South America: a Central Gondwanic Realm with endemic taxa showing affinities to Australia, New Zealand, South Africa and Namibia, a cold Perigondwanic Realm, and a warm Extragondwanic Realm with tethyan-like affinities similar to faunas of the American Midcontinent. In South America, faunas east of the southern Andes belong to the first two realms and previous interpretations of bivalve faunas suggested biocorrelations with those of the Extragondwanic Realm because they shared the taxon Heteropecten multiscalptus (Thomas). A revision of the Peruvian and Brazilian material does not confirm this. Instead, a re-analysis suggests that two species are present, rather than one: Heteropecten multiscalptus in the Cerro Prieto Formation, Amotape Mountains (Peru; Extragondwanic Realm), and Heteropecten paranaensis sp. nov. in the upper part of the Itararé Group, Paraná Basin (Brazil; Central Gondwanic Realm). Thus, the correlation between the late Palaeozoic faunas of the Central Gondwanic and Extragondwanic Realms in South America can no longer be supported. Heteropecten paranaensis sp. nov. lived in a siliciclastic-dominated, cold, epeiric sea of Brazil and Argentina, and is morphologically similar to some Australian species, whereas the Peruvian H. multiscalptus thrived in the warm seas of the Extragondwanic Realm.